Hymenopteran parasitoids associated with scale insects (Hemiptera: Coccoidea) in tropical fruit trees in the eastern Amazon, Brazil - Jesus Costa Ramos, Alberyca Stephany de; Santos de Lemos, Raimunda Norzata; Costa, Valmir Antonio; Benfatti Gonzalez Peronti, Ana Lucia [UNESP]; Silva, Ester Azedo da; Mondego, Janaina Marques; Moreira, Aldenise Alves (Florida Entomological Soc, 2018)
Fifteen species of parasitoids emerged from 6 species of scale insects, all are recorded for the first time in Maranhao State, Brazil. A total of 20 coccoid/parasitoid associations were found, 5 of which are new host records for the parasitoid species: Coccus hesperidum (L.) (Hemiptera: Coccidae) with Arrhenophagus chionaspidis (Aurivillius) (Hymenoptera: Encyrtidae); and Praelongorthezia praelonga (Douglas) (Hemiptera: Ortheziidae) with Aenasius sp. (Hymenoptera: Encyrtidae), Encyrtus aurantii (Geoffroy) (Hymenoptera: Encyrtidae), Aprostocetus sp. (Hymenoptera: Eulophidae) and Signiphora sp. (Hymenoptera: Signiphoridae).
Keywords: Aphelinidae; biological control; Encyrtidae; natural enemies; tritrophic interactions